2014
DOI: 10.1007/s00424-014-1465-7
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic stimulation reverses the I Kr–I Ks dominant pattern during cardiac action potential

Abstract: β-adrenergic stimulation differentially modulates different K+ channels and thus fine-tunes cardiac action potential (AP) repolarization. However, it remains unclear how the proportion of IKs, IKr, and IK1 current in the same cell would be altered by β-adrenergic stimulation, which would change the relative contribution of individual K+ current to the total repolarization reserve. In this study we used an innovative AP-clamp Sequential Dissection technique to directly record the dynamic –IKs, IKr, IK1– current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 30 publications
8
58
0
Order By: Relevance
“…A more interesting possibility is suggested by the results of Banyasz et al . (), who found that, although I Ks was minimal at baseline (0.152 A/F, comparable to our adjusted model), it was rapidly and dramatically enhanced over 13‐fold by β‐adrenergic stimulation (to 2.067 A/F). When run under the same conditions, I Ks in our adjusted model shows good agreement with their baseline data (0.108 A/F), whereas I Ks in the original model (1.883 A/F).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A more interesting possibility is suggested by the results of Banyasz et al . (), who found that, although I Ks was minimal at baseline (0.152 A/F, comparable to our adjusted model), it was rapidly and dramatically enhanced over 13‐fold by β‐adrenergic stimulation (to 2.067 A/F). When run under the same conditions, I Ks in our adjusted model shows good agreement with their baseline data (0.108 A/F), whereas I Ks in the original model (1.883 A/F).…”
Section: Discussionsupporting
confidence: 82%
“…However, Banyasz et al . () and Rocchetti et al . (; ) observed only minimal I Ks during AP clamp in guinea pig ventricular cardiomyocytes under baseline conditions, in agreement with our results.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Dynamic clamp experiments in guinea pig myocytes demonstrated that I Ks was larger than I Kr subsequent to β‐adrenergic stimulation (Banyasz et al . ). This is an important finding because these recordings are in conditions where [Ca 2+ ] i is not buffered and physiological membrane and Ca 2+ dynamics are maintained (Banyasz et al .…”
Section: Introductionmentioning
confidence: 97%